DISFEMISME PADA UNGGAHAN AKUN TWITTER AREAJULID - Ans, A’idah Husna Lutfiyyah; Devi, Ery Kurnia; Masdita, Fitri Icha; Ardiansyah, Muhammad Aflah (Fakultas Ilmu Budaya, Universitas Mulawarman, 2020)
This study will discuss the use of dysphemism contained in the AREAJULID Twitter account in the October 2019 edition. This study aims to describe the form, synonyms, and background of the use of dysphemism contained in the upload of AREAJULID Twitter account in the October 2019 edition. This research is a descriptive qualitative study. This research data is in the form of sentences containing dysfemism. Data were collected by referring to the note method and note technique. The data source used is the upload of the AREAJULID Twitter account in the October 2019 edition. The method of providing data is by referring to the note taking technique. Data were analyzed by the method of distribution and techniques for direct elements, sleep techniques, dressing techniques. The results of the study are: 1) the form of usage and synonymism of dysphemism in uploading the October edition of AREAJULID Twitter account 2019; 2) the background of the use of dysphemism in the upload edition of the AREAJULID Twitter account in the October 2019 edition. The form of using dysfemism in uploading the AREAJULID Twitter account in the October 2019 edition was found in two forms, namely in the form of words consisting of basic words and affixed words, and in the form of phrases. The background to using dysphemism includes: 1) declaring taboo, indecent, and pornographic things; 2) negative depictions about someone or something; 3) express irritation or anger; 4) criticize or blaspheme; 5) demean someone or something; 6) insult or reproach; 7) swearing or cursing at something.